Performance and Retention Outcomes of Secondary School Students learning Nutrient Cycle Using Biology Learning Activity Package (BIO-LAP) - Moemeke, Clara Dumebi (NIU Journal of Educational Research, 2025)
This study examined the effectiveness of the Biology Learning Activity Package (BIO-LAP) as an instructional strategy for enhancing students’ academic performance and retention in secondary school Biology in Nigeria. It also explored gender- and location-based differences in outcomes. A quasi-experimental research design was adopted, involving 157 senior secondary students drawn from both urban and rural schools. Participants were assigned to two groups: one taught using the conventional lecture method (n = 84), and the other instructed with the BIO-LAP (n = 73). Achievement and retention tests were administered, and data were analyzed using descriptive statistics and independent samples t-tests at a 0.05 level of significance. Findings revealed that students taught using BIO-LAP performed significantly better in both academic achievement and retention than those taught using the lecture method. Gender had no statistically significant effect on achievement or retention within the BIO-LAP group, indicating that the method is equally effective for male and female students. However, urban students significantly outperformed their rural counterparts in both achievement and retention, suggesting the influence of contextual factors such as access to learning resources and learning environment. The study concludes that BIO-LAP is a viable, student-centered instructional strategy capable of improving Biology learning outcomes. It recommends the adoption of BIO-LAP in science classrooms, continuous teacher training in activity-based instruction, and support for context-sensitive adaptations to bridge urban-rural disparities. The findings provide empirical backing for innovative pedagogies that align with national goals of improving STEM education quality and equity. Keywords: Biology learning activity, LAP, science education, science teaching, biology education, retention, performance biology education